ANALISIS GAYA HIDUP (LIFESTYLE) SEBAGAI FAKTOR RESIKO PENYAKIT GAGAL GINJAL KRONIS - Diyono Diyono; Ratna Indriati (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background : globally, nationally, and regionally, chronic renal failure tends to increase.The most effective therapy for chronic renal failure is the prevention of risk factors.Objectives : identify lifestyles in the form of high-fat diet habits and consumption ofenergy supplements as a risk factor for chronic renal failure.Methods : this research is a correlation research with case control design. The samplewere 75 case study groups and 75 control groups. Data obtained through interviews andanalyzed using multiple logistic regression with SPSS series 18.Results : lifestyle that affect the incidence of chronic renal failure is high fat dietary habits(p = 0.001; OR = 0.256; CI = 0.116 - 0.562), consumption of energy supplements (P =0.001; OR = 0.229; CI = 0.094 - 0.560).Conclution : research conclusions are high-fat dietary habits and consuming energysupplement drinks is a lifestyle that affects the increased risk of chronic renal failure.Keyword : Chronic Kidney Desease, Lifestyle, Risk Factors.